-(w+3)=-4x+10

Simple and best practice solution for -(w+3)=-4x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(w+3)=-4x+10 equation:


Simplifying
-1(w + 3) = -4x + 10

Reorder the terms:
-1(3 + w) = -4x + 10
(3 * -1 + w * -1) = -4x + 10
(-3 + -1w) = -4x + 10

Reorder the terms:
-3 + -1w = 10 + -4x

Solving
-3 + -1w = 10 + -4x

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1w = 10 + 3 + -4x

Combine like terms: -3 + 3 = 0
0 + -1w = 10 + 3 + -4x
-1w = 10 + 3 + -4x

Combine like terms: 10 + 3 = 13
-1w = 13 + -4x

Divide each side by '-1'.
w = -13 + 4x

Simplifying
w = -13 + 4x

See similar equations:

| 30x+9=11 | | 6x+60=90 | | (33.333)9cubed= | | 3b+16a-9n= | | -8x+5=-75 | | x^2-16x+89=0 | | 18x+7=29 | | (2w-3)(6-w)=0 | | (3x-5)=0 | | N+.5n=63 | | 0.7x+0.5=0.9x-0.7 | | 8(x+3)=4x+5 | | 3(y+7)=2(y+8) | | 6x+4=32 | | 2x-10-8=24-16-8x | | .143(49-7y)=14 | | -5(2-5x)+(-8x-2)=-4x-8x | | 6b=348 | | 15x/7=11/7 | | 3m-9x-1=24 | | 5-(.5)g=12 | | 5(4x-7)+13x-20=8(x+10)-15x+65 | | 15x/7=0 | | -[8z-(18z+3)]=3+(9z+10) | | 11x+2=10x+4 | | 92=2h | | X*1+2*0.6=2+X*0.9 | | 2c^2-c-6= | | -196=-9.8x^2 | | 9p+2=4+8p | | 2x+1=-(9) | | 6x^2-23x=7 |

Equations solver categories